A Lower Energy Balance is Associated With Higher Severity and Odd of Depression Based on the Beck Depression Inventory‐13 (BDI‐13) in a Retiring Age Population: A Population‐Based Cross‐Sectional Study - Mohammad Reza Shadmand Foumani Moghadam; Mostafa Shahraki Jazinaki; Zohre Hosseini; Fatemeh Rajabi; Sharif Etemdi; Melika Hadizadeh; Parnian Pezeshki; Mohammad Amushahi; Reza Rezvani (Health Science Reports)
ABSTRACT Background and Aims Depression is a mental disorder, especially in aging people. Many studies worked on the association of diet with depression, but the association of energy is still unclear. This study aims to investigate the relationship between energy balance and the risk of depression in a retiring‐age population. Methods In this population‐based cluster‐sampling cross‐sectional approach, a total of 765 retiring‐age individuals were categorized into different levels of depression using the Beck Depression Inventory‐13 (BDI‐13). Energy balance was calculated by subtracting energy intake from Total Energy Expenditure (TEE) and Basal Metabolic Rate (BMR) which was calculated using Bio‐Electrical Impedance Analysis and Mifflin and St‐Jeor formula. Results There was a significant difference in energy intake, BMR, TEE, and energy balance between depression groups (p < 0.003 for all factors). However, by stratifying to gender, only energy intake, TEE, and energy balance according to BMR stayed significant. There was a trend towards lower energy intake and more negative energy balance with increasing severity of depression especially in males. After adjusting for various factors in all models, the results remained mostly consistent, except in Models 3 and 4 which were adjusted for nutrient intake patterns, health quality (12 domains), and supplement intake. There was a significantly weak negative correlation between the BDI‐13 score and all factors which was stronger in males.